Behavioural finance and its impacts on portfolio management decision: evidence in Malaysia - Chai, Hui Xin; Chew, Jing Han; See, Yi Zhen; Soh, Ai Waye; Song, Kar Jing (2021)
In order to examine whether the behavioural biases play a role in affecting the Malaysian’s investment decision making, this study which concerns the relationship between the investment decision made by Malaysian investors and several behavioural biases was conducted. There was a total of 163 respondents who took part in this study through online platform. In this study, the statistical results of Cronbach’s alpha, composite reliability, average variance extracted (AVE), discriminant validity, and hypotheses testing were obtained through the execution of Partial Least Squares Structural Equation Modeling (PLS-SEM). Besides, this study discovered some of the studied biases which are overconfidence bias, representativeness bias, and herding bias possessed significant relationship with the investment decision made by Malaysian investors while the others which includes regret aversion bias and loss aversion bias did not. It is observed that the Malaysian investors tend to be overconfident, stereotyped, and relied on others’ information while making their investment decisions. On the other hand, they are not afraid of making investment decision even though it could possibly cause them to be regretful or suffer loss. At last, this study serves to provide insights and recommendations for multiple parties such as the society, investors, investment advisors, and corporations.